(untitled) (Acta Polytechnica CTU Proceedings, 2020)
Mechanical characterization of plasma-sprayed coatings at microscopic level represents a major challenge due to the presence of numerous inherent microstructural features such as cracks, pores, or splat boundaries, which complicate coatings characterization by conventional testing methods. Need for reliable testing of structural integrity of newly developed multiphase plasma-sprayed coatings introduced even more complexity to the testing. In this study, applicability of indirect vibratory cavitation test (adapted from ASTM G32 standard) for such testing was evaluated. Three plasmasprayed coatings having distinctive microstructures were tested: i) conventional alumina coating deposited from coarse powder, ii) hybrid coating deposited by co-spraying of coarse alumina powder and fine yttria-stabilized zirconia (YSZ) suspension, and iii) compact alumina coating deposited from fine ethanol-based suspension. Differences in the coatings internal cohesion were reflected in different failure mechanisms observed within the cavitation crater by scanning electron microscopy and mean erosion rates being i) 280 μm/hour, ii) 97 μm/hour and iii) 14 μm/hour, respectively.